2016
DOI: 10.1111/cea.12743
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of plasma levels of specific IgE in chlorhexidine allergic patients with and without accidental re‐exposure

Abstract: Time from reaction should be considered when interpreting specific IgE results. Specific IgE is >0.35 kUA/L in most patients at time of reaction but should be repeated after a few weeks/months if negative. The optimal sampling time seems to be >1 month and <4 months. A value <0.35 kUA/L neither excludes allergy nor implies loss of reactivity in previously sensitized patients. Re-exposures are common, often iatrogenic, and can cause a rebound in specific IgE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
0
37
0
1
Order By: Relevance
“…Interestingly, his specific IgE tests remained negative on repeat testing over 6 months. A study of patients with chlorhexidine anaphylaxis showed that only 1 out of 23 had a negative specific IgE test 2–4 months after the reaction 28. The reason for the negative results in our patient may be a reflection of the fact that patients with renal failure appear to have lower levels of IgE in general 29…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, his specific IgE tests remained negative on repeat testing over 6 months. A study of patients with chlorhexidine anaphylaxis showed that only 1 out of 23 had a negative specific IgE test 2–4 months after the reaction 28. The reason for the negative results in our patient may be a reflection of the fact that patients with renal failure appear to have lower levels of IgE in general 29…”
Section: Discussionmentioning
confidence: 59%
“…Two‐thirds of children had to wait more than 12 weeks to be seen, while more than half of adults waited more than 8 weeks to be seen which may impact on test sensitivity. Drug sensitization to chlorhexidine is known to be transient so these delays in assessment run the risk of missing important sensitizations and compromising the diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Optimum sampling time appears to be between 1-4 months. The authors noted, however, that levels <0.35KUA/L could not be used to rule out hypersensitivity to chlorhexidine [7]. Patients with eczema, especially those with leg ulcers or leg eczema, are especially prone to chlorhexidine allergies [8].Anaphylactic reactions have been reported after the use of chlorhexidine including during normal bladder catheterization [9,10].Irreversible corneal injuries and opacification attributed to chlorhexidinegluconate 4% topical preparation, are reported in 4 female patients, aged 9 months to 83 years, in whom the drug was accidentally introduced into the eye during surgical preparation.…”
Section: Topical Antiseptics Chlorhexidinementioning
confidence: 99%